2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path652>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, proliferation, and angiogenesis in oral tissues. Possible relevance to tumour progression

Abstract: Experimental animal models have demonstrated that angiogenesis is essential for tumour progression, whilst sustained tumour growth requires a positive balance between tumour cell proliferation and cell death (apoptosis). The aim of this study was to determine the relative contribution of apoptosis, proliferation, and angiogenesis to disease progression in the oral mucosa. Histological sections of 47 archival specimens were examined; these included four groups of oral tissues: normal mucosa (n=12), moderate dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 28 publications
7
36
1
1
Order By: Relevance
“…The amount of apoptosis seen in carcinomas varied ( Figure 1B), with a range of apoptotic indices from 0.03 to 2.25%. The amount of apoptosis that we observed in the TUNEL assay was generally similar to that reported by others (Xie et al, 1999;Macluskey et al, 2000;Stoll et al, 2000). The late stages of apoptosis that result in the distinctive morphology of an apoptotic cell are thought to occur rapidly, followed by phagocytic removal of the apoptotic bodies by neighbouring cells.…”
Section: Resultssupporting
confidence: 89%
“…The amount of apoptosis seen in carcinomas varied ( Figure 1B), with a range of apoptotic indices from 0.03 to 2.25%. The amount of apoptosis that we observed in the TUNEL assay was generally similar to that reported by others (Xie et al, 1999;Macluskey et al, 2000;Stoll et al, 2000). The late stages of apoptosis that result in the distinctive morphology of an apoptotic cell are thought to occur rapidly, followed by phagocytic removal of the apoptotic bodies by neighbouring cells.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have shown that vascularity increased in a stepwise fashion from normal mucosa through dysplasia to carcinoma, suggesting that disease progression in the oral mucosa is accompanied by angiogenesis [4][5][6][7][8][9]. In contrast our study showed no significant difference in vascularity between normal mucosa and leukoplakia, but a statistically significant difference was found between normal mucosa vs. carcinoma (P<0.001), and leukoplakia vs. carcinoma (P<0.001).…”
Section: Angiogenesis and Carcinoma Developmentcontrasting
confidence: 90%
“…The expression of angiogenic activity has been shown to be an early and predictable characteristic of many pre-neoplastic cells, and may represent one of the earliest indications that a cell population has become committed to malig-nancy [3]. Studies have shown that vascularity increases from normal mucosa to moderate dysplasia to carcinoma [4][5][6][7][8][9]. Head and neck squamous cell carcinoma (HNSCC) have a high tendency to spread to adjacent sites and to the cervical lymph nodes (LNs), whereas their distant metastatic potential is very low [10].…”
mentioning
confidence: 99%
“…By using an experimental animal model, it was shown that the initiation of angiogenesis appeared concomitantly with a decrease in the tumour cell apoptosis, while the levels of the tumour cell proliferation remained constant, thus leading to the net tumour growth [10]. The preinvasive malignant cells are known to remain dormant until they become angiogenic, and this is followed by a phase of rapid tumour growth [15,16].…”
Section: Discussionmentioning
confidence: 99%